Frederik II og truslen fra de katolske magter LINJER I DANSK UDENRIGSOG SIKKERHEDSPOLITIK 1571-88 - P. Jensen, Frede (Historisk Tidsskrift, 1993)
This study attemps to show how the Danish State leadership reacted to the problems caused by the international situation and Denmark's geostrategic position during the years 1571-1588. The challenges were altogether considerable, but the favorable position as an island of peace between the different war zones of the era created opportunities for an elimination of different security weaknesses and an assertion and enforcement of Danish sovereignty positions. A constant challenge was Sweden, where the rapprochement between king Johan 111 and the Catholic powers during the 1570s was accompanied by a policy of plots and intrigues against Denmark. However, the Danish state leadership managed to assert its interests vis-a-vis the neighbouring powers of Sweden and Poland in the Baltic area and forced through an abandonment of Poland's naval plans. Similarly, the new important source of revenue, lastetolden, was consolidated without major problems. The prerequisites for the country's significantly strengthened international position in the 1580s must be related to the economic consolidation and the ambitious naval build-up, which, tanks to the construction of new big vessels, turned the navy into one of the most powerful in Europe. Also significant was the military strengthening of the Danish core area around the Sound achieved by important fortifications, notably at Elsinore. But it was equally essential that king Frederik II asserted sovereignty and status and pursued a maritime policy with determination and consistency.